Clinical and cVEMP Evaluation Predict Short-Term Residual Dizziness After Successful Repositioning in Benign Paroxysmal Positional Vertigo - Jiang, Chun-Yan; Wu, Jing; Shu, Liang; Sun, Xu-Hong; Pan, Hui; Xu, Qian; Wu, Si-Cheng; Liu, Jian-Ren; Li, Yun; Chen, Wei (Frontiers in Medicine, 2022)
Objective: Residual dizziness (RD) is a frequent symptom with unknown pathogenesis, often complained about by patients with benign paroxysmal positional vertigo (BPPV), even after successful canalith repositioning procedure (CRP). The present study aims to quantitatively evaluate the short-term RD severity and its risk factors in patients with BPPV after successful CRPs. Methods: Two hundred and twenty BPPV patients after successful CRPs (W0) were prospectively followed up for 1 week (W1). Besides demographics and serial neuropsychological assessments (including dizziness handicap inventory-DHI, etc), patients also received cervical/ocular vestibular evoked myogenic potential (c/oVEMP) evaluation. RD was defined as patients with dizziness or imbalance, dizziness visual analog scale (VAS) >1 and without positional vertigo or nystagmus at W1. Demographic, clinical and VEMPs differences were compared among the three groups: patients with minor (dizziness VAS 1 3), moderate to severe (dizziness VAS >3) and without RD. Results: The total frequency of RD at W1 was 49.1%(n=108), with 32.3%(n=71) minor, and 16.8%(n=37) moderate to severe RD. Logistic regression analyses revealed that RD was closely associated with DHI status (OR=2.101, P=0.008) at W0, this effect was not present for minor RD. In addition to DHI score >30 (OR=4.898, P<0.001) at W0, bilateral cVEMP absence (OR=4.099, P=0.005) was also an independent influential factor of moderate to severe RD. Conclusion: Our study highlights the importance of RD quantified evaluation. DHI score >30 and bilateral cVEMP absence could increase the risk of short-term moderate to severe RD.